VERTIGO AND DIZZINESS IN ANTERIOR CIRCULATION CEREBROVASCULAR DISEASE : SYSTEMATIC REVIEW - Annurul Maulidia, Agnes; Rimbun Silitonga, Anni Rota (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Recurrent spontaneous vertigo/dizziness episodes may manifest as fleeting occurrences. It is uncommon for vascular vertigo to cause an isolated positional vestibular condition, also known as recurrent positional vertigo or disorientation. The anteriormost boundary of the structure is the solitary anterior communicating artery (ACom), which connects the ring to the bilateral anterior cerebral arteries (ACA).The aim: This article explore about vertigo and dizziness in anterior circulation cerebrovascular disease.Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done.Result: In the PubMed database, the results of our search brought up 12 articles, whereas the results of our search on SagePub brought up 6 articles. The results of the search conducted for the last year of 2013 yielded a total 7 articles for PubMed and 2 articles for SagePub. In the end, we compiled a total of five papers, 4 of which came from PubMed and one of which came from SagePub. We included three research that met the criteria.Conclusion: Previous research has linked the findings of vertigo with disturbances in the cerebral arteries, especially when accompanied by complaints of hearing loss, balance disturbances, and limb weakness.